Efek suhu sintering dan komposisi bahan terhadap karakteristik mekanik komposit berbahan limbah aluminium dan kaca menggunakan metode metalurgi serbuk - Triadi, A.A. A.; Wangi, K. G.K.; Setyawan, P. D. (Universitas Mataram, 2022)
The waste has been a big problem for human and environment and has become a hot issue until recently. One of the wastes that we often encounter is aluminum waste. Aluminum waste can indeed be re-melted, but the results of the smelting will produce even more dangerous waste, namely Toxic Hazardous Material) waste. In addition to aluminum waste, there is also a lot of waste that we encounter in our daily lives, namely glass waste. This study aims to maximize the potential of aluminum waste and glass waste by examining the effect of variations in sintering temperature and material composition on the hardness and compressive strength of the composite. This research is started by crushing the solid material into the mesh of 100, the next stage is mixing the powder and then print it with 7 tons pressure load. The last step is sintering the specimens at temperatures of 390oC, 490oC, and 590oC with 60 minutes holding time. The results show that the highest hardness value is 60 HRF and the highest compressive strength value is 235.59 MPa. Macrostructure observation shows that there is greater porosity in the specimen with lower mechanical properties. Variation of sintering temperature has a directly proportional effect on the hardness and compressive strength values. Variation in the composition of material gives an inversely proportional effect on the two tests of mechanical properties when viewed from the percent addition of glass powder.